PEMBUATAN DAN IMPLEMENTASI MODUL PRAKTIKUM FISIKA BERBASIS MASALAH UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA KELAS XI (UPEJ Unnes Physics Education Journal, 2012)
Experimental studies have been conducted to improve the independence of students, through problem based learning model with problem-based physics lab module. It is based on the lack of independence of the students, so that their learning can not achieve maximum learning outcomes. Samples were taken at random and obtained two samples of the class as a class XI Science XI IPA 4 and 5. Further retrieval using a questionnaire that had been tested experts. The analysis used in this study etc: testing the equality of two variances, test for normality using the chi-square formula, the gain test. The results of this study, has successfully created modules like the syntax module manufacturing. The module contains a solution with practical problems. Step application in classes based on the syntax of learning using PBL models. The results showed that learning with problem-based physics lab module can increase student independence. And increase student independence was followed by an increase learning outcomes.